Cover Image. (9th February 2021) - Muñoz, Nicolas J.; Reid, Brian; Correa, Cristian; Neff, Bryan D.; Reynolds, John D.
Abstract : The cover image is based on the Original Article Non‐native Chinook salmon add nutrient subsidies and functional novelty to Patagonian streams, by Nicolas J. Muñoz et al., https://doi.org/10.1111/fwb.13655 .